KAJIAN LUASAN DAERAH TANGKAPAN HUJAN DAN RANCANGAN DIMENSI SALURAN TERBUKA JALAN ANGKUT DI PT. LINTAS ARTHA KOTA SORONG PROVINSI PAPUA BARAT - Ferdian Manibuy; Hendri P. Perangin-Angin (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
Lintas Artha is a mining company with an open mining system where its activities are directly related to outside air. Topographical conditions in the form of a plateau which has a height of ± 44m-62m above sea level (dpl). The mining location is on a hill, so the weather is very uncertain. Influencing mining activities, the company needs to pay attention to the proper drainage system to prevent or control water entering the mining location from rainwater and runoff. Therefore, a technical study of the flow system on the haul road will be carried out. Based on the calculation, it is found that the area of the rain catchment area is 24,400 km2, the dimensions of the open channel in the haul road area have a channel bottom width of 1m, a water guard height of 0.6m, a channel slope of 60°. Then we get a trapezoidal channel that can flow a discharge of 33.33m3/second.